Chronic rate dependent exit block after pulmonary vein isolation. (3rd April 2021) - Makker, Parth; Dulmovits, Eric; Beldner, Stuart
Abstract: Rate dependent exit block across the pulmonary veins has been previously described immediately following catheter ablation. We report a case of rate dependent pulmonary vein exit block seen at repeat ablation 7 years after the index procedure. To our knowledge, this is the first report of chronic rate dependent exit block discovered years after circumferential pulmonary vein antral isolation.